التفسير الصوفي الإشاري في أعمال القلوب: دراسة نقدية في البحر المديد لابن عجيبة - Hashim, M.; Abdulrahman Obeid; Mohamed Yusoff, A. (Universiti Sains Islam Malaysia, 2024)
The research aims to define Tafsir Sufi Ishaari and Tafsir Al Bahr Al-Madid by Ibn Ajibah (1809). The research as well will extrapolate Tafsir Sufi Ishaari for Quranic verses in the book which related to the issue of the heart purification. The methodology-for this research in analyzing information depends on the descriptive approach, and on collecting all facts and information. It also uses the analytical and criticism approach by matching the scholarly conditions of acceptance regarding Tafsir Sufi Ishari with what was interpreted by Ibn Al Ajibah. Then compare, evaluate and criticize it. Therefore, the findings indicate that the Tafsir Sufi Ishari-which is one of the types of the Quranic exegesis based on interpretations of verses contrasts the classical commentaries- by Ibn Ajibah in the issue of the heart purification that matching the conditions were based on two foundations. Firstly: The Tafsir Sufi Ishari was interpreted accordingly to general verses meaning and exegesis. Secondly: The relationship between Tafsir Sufi Ishari to al-Ma'thur is like the relationship causes and effect. The study also revealed that the contradictions with conditions ion Tafsir Sufi Ishari in this issue are based on three foundations. Firstly : interpretations of Ibn Ajibah were so far from the common use of Arabic understanding. Secondly: The interpretations made were analogous compared to other normal exegesis. Thirdly: to generalize some issues which are strictly individuals. In facts, if Ibn Ajibah limited his interpretation to his Ishari views there is no differences between him and the doctrine of Shiites Batiniyyah!, But our trust in his scholary' Tafsir, his confirmation of classical interpretation and his condemnation of Batiniyyah understanding make his Tafsir Ishari valid and well concerned.